2010
DOI: 10.1182/blood-2009-07-234690
|View full text |Cite
|
Sign up to set email alerts
|

Directed differentiation of hematopoietic precursors and functional osteoclasts from human ES and iPS cells

Abstract: The directed differentiation of human pluripotent stem cells offers the unique opportunity to generate a broad spectrum of human cell types and tissues for transplantation, drug discovery, and studying disease mechanisms. Here, we report the stepwise generation of bone-resorbing osteoclasts from human embryonic and induced pluripotent stem cells. Generation of a primitive streak-like population in embryoid bodies, followed by specification to hematopoiesis and myelopoiesis by vascular endothelial growth factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
92
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(94 citation statements)
references
References 51 publications
2
92
0
Order By: Relevance
“…Induced pluripotent stem cells (iPSCs) are pluripotent cells derived from terminally differentiated cells by dedifferentiation. The generation of iPSCs creates the possibility of generating tissue-specific cells, including HSCs [63][64][65][66][67][68] or MSCs [69][70][71][72][73][74][75][76], but further study is required before clinical application of iPSCs can commence. Taken together, immune reconstruction and modification of genetic predisposition of hematopoietic stem cells are important for radical cure of IBD.…”
Section: Intestinal Stem Cells and Other Stem Cells In Ibdmentioning
confidence: 99%
“…Induced pluripotent stem cells (iPSCs) are pluripotent cells derived from terminally differentiated cells by dedifferentiation. The generation of iPSCs creates the possibility of generating tissue-specific cells, including HSCs [63][64][65][66][67][68] or MSCs [69][70][71][72][73][74][75][76], but further study is required before clinical application of iPSCs can commence. Taken together, immune reconstruction and modification of genetic predisposition of hematopoietic stem cells are important for radical cure of IBD.…”
Section: Intestinal Stem Cells and Other Stem Cells In Ibdmentioning
confidence: 99%
“…Previous studies have demonstrated that hESCs can differentiate into hematopoietic progenitor cells/stem cells (HPCs/HSCs) through the formation of embryoid bodies (EBs), or co-culture with hematopoiesis-supporting stromal cells, such as the OP9, S17 and AM20.1B4 cell lines [1][2][3][4][5]. Recent studies have shown that iPS cells can also differentiate into HPCs [6,7]. However, these differentiation approaches have considerable drawbacks, such as being uncommitted and undefined, making them not optimal for studying the mechanisms of human hematopoietic development.…”
Section: Introductionmentioning
confidence: 99%
“…22 Another study reported that a step-wise generation of osteoclasts from iPSCs yielded a monocyte-macrophage lineage population using defined factors in the absence of serum and feeder cells through an EB formation intermediate. 23 Aside from using EB formation to guide iPSCs into the hematopoietic lineage, mouse OP9 stromal cells can also be harnessed to direct the differentiation of hiPSCs through coculture. Choi et al 24 used this system to generate hematopoietic cells from seven hiPSC lines, finally obtaining CD34 1 CD43 1 hematopoietic progenitors.…”
Section: Ipscs Can Redifferentiate Into To Hscsmentioning
confidence: 99%